Conformable superoleophobic surfaces with multi-scale structures on polymer substrates. Issue 21 (9th May 2016) - Cho, Handong; Jeong, Jonghyeon; Kim, Wook; Choi, Dukhyun; Lee, Sangmin; Hwang, Woonbong
Abstract : Multi-scale structures combining Cu(OH)2 nanowire arrays and AlO(OH) nanoflake structures are utilized for easily adaptable superoleophobic surfaces. Abstract : The preparation of superoleophobic surfaces has attracted considerable attention, but the practical application of previously reported methods is still difficult owing to the required complicated wafer process and lack of adaptability to any target objects. In this study, we successfully developed a highly conformable superoleophobic surface on a flexible polypropylene film using multi-scale structures and surface functionalization. The multi-scale structures are fabricated via the formation of nanowire arrays and attachment of nanoflakes, realized by inexpensive and easy fabrication processes. Then, after deposition of a fluoroalkylsilane coating, the structured surface shows superoleophobicity with high contact angles and low sliding angles for various liquids with surface tensions as low as 23.8 mN m −1 . We also realized a patterned surface with extremely different wettabilities by tailoring the surface geometry and surface energy. Further, the wetting properties of the fabricated surface were maintained during repeated bending and twisting tests (10 000 cycles) and under shrinkage deformation ( ε shrink = 10%). Thus, the proposed strategy represents a facile method to develop easily adaptable surfaces with special wettabilities.